The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/acs.jpcc.5b08946
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Free-Standing Features of Stanene/Stanane on InSe and GaTe Nanosheets: A Computational Study

Abstract: Two-dimensional tin and its iodized derivative, called stanene and stanane, are intriguing nanomaterials as quantum spin Hall (QSH) insulators. A recent experiment on stanene has found that the strong interaction from substrates will disturb the Dirac cones and cause a metallicity problem into stanene [F. Zhu et al. Nat. Mater. 2015, 14, 1020. On the basis of van der Waals density functional calculations, we find that stanene and stanane can form commensurate van der Waals heterosheets with InSe and GaTe laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 45 publications
(89 reference statements)
0
10
0
1
Order By: Relevance
“…Various approaches have been taken to modulate the electronic properties of stanene. [24][25][26][27][28] Tang et al 27 demonstrated that functionalization on stanene can open up the gap. Furthermore, the substrate plays an important role to tune the electronic properties of stanene due to the strong interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various approaches have been taken to modulate the electronic properties of stanene. [24][25][26][27][28] Tang et al 27 demonstrated that functionalization on stanene can open up the gap. Furthermore, the substrate plays an important role to tune the electronic properties of stanene due to the strong interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the substrate plays an important role to tune the electronic properties of stanene due to the strong interaction. 25,29 Electronic properties of stanene are affected by the substrate because it induces band inversion in the bonding and antibonding states of stanene, which opens up the band gap in stanene. 27 Furthermore, van der Waals heterostructure of stanene modulates its electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Quasi-2D GaTe/GaSe heterostructure was created by transferring exfoliated few-layer GaSe onto bulk GaTe sheets and found to form type I band alignment at the interface [ 29 ]. The GaTe/SnI heterostructure was verified to be a large-gap quantum spin Hall insulator and exhibits a noticeable Rashba splitting that can be modulated by changing the interlayer distance of heterosheets [ 30 ]. In addition, construction of semiconductor/C 2 N heterostructures, such as g-C 3 N 4 /C 2 N [ 31 ], MoS 2 /C 2 N [ 32 ], and CdS/C 2 N [ 33 ], demonstrated an enormous potential for promoting the photocatalytic performance of C 2 N due to the efficient separation of the electron-hole pairs, thereby restraining the recombination of photogenerated carriers.…”
Section: Introductionmentioning
confidence: 99%
“…This fascinating proposal immediately boosted the search for 2D TIs, although it has been ruled out for the case of graphene itself due to the negligible SOI. In recent years, besides QW structures, various atomically thin mono or few layers have been studied mostly theoretically to peruse nontrivial topological phases in 2D materials [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] . These atomically thin crystals usually consist of either an element from group III to group VII or some certain transition metal compounds, although among them there are complex structures like organometallic lattices (for a decent review see Ref.…”
Section: Introductionmentioning
confidence: 99%